Factors Influencing the Consumer Decision-Making Process for Residential Solar Panel Purchases in Chonburi Province - Rienrungrote, Atisak; นิธิเชาวกุล, ธนภณ; นนทแก้ว แฟร์รี่, กัญจนวลัย (Journal of MCU Phetchaburi Review, 2025)
This research aims to 1) To study the marketing mix factors and perceived value that directly influence the decision-making process in purchasing residential solar panels. 2) To examine the marketing mix factors that directly influence the perceived value of residential solar panels. 3) To investigate the marketing mix factors that indirectly influence the decision-making process through perceived value regarding residential solar panels, consistent with empirical data. This is a quantitative research study, utilizing a questionnaire as the research instrument. Reliability and validity were measured using Cronbach's alpha and the Index of Item-Objective Congruence (IOC), with values exceeding 0.50 indicating content validity. This methodology follows the guidelines of Supamas Angsuchoti et al. (2009), which recommend a sample size of 20 times the number of observable variables. The research collected data from 356 respondents through purposive sampling targeted at electricity users interested in energy savings and the use of solar panels. Descriptive statistics, including percentages and means, were employed to analyze the data. Additionally, causal analysis was conducted using Structural Equation Modeling (SEM). The findings revealed that the marketing mix has a direct influence on the perceived value and decision-making process of consumers purchasing residential solar panels in Chonburi Province, with complete mediation at a statistical significance level of 0.001. The perceived value has a direct influence on the decision-making process, also with complete mediation, at a statistical significance level of 0.05. The marketing mix exerts an indirect influence through perceived value on the decision-making process, with complete mediation, at a statistical significance level of 0.05. This aligns with the concept of value creation using marketing mix strategies to promote the use of renewable energy within communities. This research contributes to expanding the body of knowledge in clean energy marketing and can be applied to develop proactive strategies to promote the decision-making process for purchasing solar panels at both community and national levels.